Correlation between Serum Ferritin, Serum Cystatin C, and Renal Function in Children with β Thalassemia Major - Suci Saptyuni Permadi; Lelani Renarti; Dedi Rachmadi (Majalah Kedokteran Bandung, 2019)
Renal dysfunction caused by iron overload is characterized by an increase in ferritin and cystatin C levels. The objective of this study was to determine the correlation between ferritin, cystatin C, and renal function in children with β thalassemia major. A cross-sectional observational analytic study was conducted in September 2018 on 34 children with β thalassemia major in Dr. Hasan Sadikin General Hospital. Ferritin and cystatin C levels were documented and the estimated glomerular filtration rate (eGFR) was calculated using the Schwartz formula. Statistical tests were performed using Rank Spearman and Point Biserial with p value of <0.05 considered significant. the median ferritin level, cystatin C level, and eGFR of the subjects were 2,818 ng/mL (95% CI: 2,505–3,977), 209.9±121.5 (95% CI: 167.5–252.3), and 185.5 mL/min /1.73 m2 (95% CI: 173.6–208.2), respectively. Correlations were sought between serum ferritin and eGFR (r=0.132, p=0.229), between cystatin C and eGFR: r=0.3012, p=0.041, and between ferritin and cystatin C: r=0.433, p=0.011. No correlation was found between ferritin and renal function whereas serum cystatin C presented a positive correlation with renal function. A strong correlation was found between ferritin and cystatin C. Serum ferritin and cystatin C are promising biomarkers to assist in monitoring renal function in children with β thalasemia major.